(untitled) (Ustozlar uchun, 2025)
This article explores the experiences and insights gained during a teaching practicum in English language classes. It focuses on the transition from theoretical knowledge to practical application, highlighting the challenges and successes encountered. Through detailed observations and reflections, the study examines the development of teaching skills, classroom management strategies, and student engagement techniques. The findings offer valuable perspectives for aspiring teachers, emphasizing the importance of practical experience in shaping effective teaching practices and enhancing professional growth. This journey from school practice to future teaching underscores the transformative impact of real-world classroom exposure on a student's path to becoming an educator.